ความสัมพันธ์ระหว่างการเปลี่ยนผู้สอบบัญชี และความเห็นของผู้สอบบัญชีในปีก่อนกับการจัดการกำไรของบริษัทจดทะเบียนในตลาดหลักทรัพย์แห่งประเทศไทย - ศศิพิมพ์ อัศตรกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The purpose of this thesis is to analyze the relationship among auditor changes, prior auditor’s opinion and earnings management of listed companies in the Stock Exchange of Thailand (SET). Earnings management was measured by using discretionary accrual based on cross-sectional modified Jones model (1991) employing balance sheet and cash flow based approach alternatively. The population included the listed companies with auditor changes, except for those in financial business, during the year 2002 and 2006. This study is an empirical study. Both descriptive statistics and multiple regression were used to analyze the data. The results of this study show that, at 95 % confidence interval, earnings management does not significantly correlate with auditor changes both in balance sheet and cash flow based approach. In addition, earnings management measured by discretionary accrual using balance sheet approach does not significantly correlate with prior year auditor’s opinion. However, the two variables are significantly correlate when earnings management was calculated using cash flow based approach. Moreover, the results of control variables show that change in cash flow from operating activity, debt to equity ratio (leverage) and company’s size correlate significantly with earnings management.